The activation of nicotinic acetylcholine receptors enhances the inhibitory synaptic transmission in the deep dorsal horn neurons of the adult rat spinal cord - Gu Jianguo G; Nakatsuka Terumasa; Takeda Daisuke; Yoshida Munehito (SAGE Publishing, 2007)
Abstract Somatosensory information can be modulated by nicotinic acetylcholine receptors (nAChRs) in the superficial dorsal horn of the spinal cord. Nonetheless, the functional significance of nAChRs in the deep dorsal horn of adult animals remains unclear. Using whole-cell patch-clamp recordings from lamina V neurons in the adult rat spinal cord, we investigated whether the activation of nAChRs could modulate the inhibitory synaptic transmission in the deep dorsal horn. In the presence of CNQX and APV to block excitatory glutamatergic synaptic transmission, bath applications of nicotine (100 μM) significantly increased the frequency of spontaneous inhibitory postsynaptic currents (sIPSCs) in almost all neurons tested. The effect of nicotine was mimicked by N-methyl-4-(3-pyridinyl)-3-butene-1-amine (RJR-2403, 100 μM), an α4β2-nAChR agonist, and was also mimicked by choline (10 mM), an α7-nAChR agonist. The effect of nicotine was completely blocked by the nAChR antagonist mecamylamine (5 μM). In the presence of tetrodotoxin (0.5 μM), nicotine (100 μM) significantly increased the miniature IPSC frequency. On the other hand, RJR-2403 (100 μM) or choline (10 mM) did not affect miniature IPSCs. The application of nicotine (100 μM) also evoked a large inward current in all lamina V neurons tested when cells were held at -60 mV. Similarly, RJR-2403 (100 μM) induced inward currents in the majority of lamina V neurons examined. On the other hand, choline (10 mM) did not elicit any detectable whole-cell currents. These results suggest that several nAChR subtypes are expressed on the presynaptic terminals, preterminals, and neuronal cell bodies within lamina V and that these nAChRs are involved in the modulation of inhibitory synaptic activity in the deep dorsal horn of the spinal cord.